The big break : the greatest American WWII POW escape story never told - Dando-Collins, Stephen (St. Martin's Press, 2017)
"Oflag 64, a World War II prisoner of war (POW) camp based in Schubin, Poland, was speculated to be one of the only POW camps set up exclusively for U.S. Army ground component officers. About 150 American officers lived in the camp in 1943, and by 1945, that number had expanded to 1,500. When the German commandant Colonel Fritz Schneider received orders to march all of his prisoners to west Germany to escape the Russians in January 1945, that number declined rapidly as the American officers put into place long-existing escape plans that would make history. In The Big Break, we follow famous POWs, such as General Eisenhower's personal aide, General Patton's son-in-law, and Ernest Hemingway's eldest son, as the first American escapes via a tunnel in a stinking latrine, with almost 250 US officers following closely behind in a mass break. Historian Stephen Dando-Collins chronicles the gripping story of irrepressible Americans determined to be free, brave Poles risking their lives to help them, and dogmatic Nazis determined to stop them"--